Stacking interactions between carbohydrate and protein quantified by combination of theoretical and experimental methods - Wimmerová, Michaela; Kozmon, Stanislav; Nečasová, Ivona; Mishra, Sushil Kumar; Komárek, Jan; Koča, Jaroslav (PloS one, 2012)
Carbohydrate-receptor interactions are an integral part of biological events. They play an important role in many cellular processes, such as cell-cell adhesion, cell differentiation and in-cell signaling. Carbohydrates can interact with a receptor by using several types of intermolecular interactions. One of the most important is the interaction of a carbohydrate's apolar part with aromatic amino acid residues, known as dispersion interaction or CH/π interaction. In the study presented here, we attempted for the first time to quantify how the CH/π interaction contributes to a more general carbohydrate-protein interaction. We used a combined experimental approach, creating single and double point mutants with high level computational methods, and applied both to Ralstonia solanacearum (RSL) lectin complexes with α-L-Me-fucoside. Experimentally measured binding affinities were compared with computed carbohydrate-aromatic amino acid residue interaction energies. Experimental binding affinities for the RSL wild type, phenylalanine and alanine mutants were -8.5, -7.1 and -4.1 kcal x mol(-1), respectively. These affinities agree with the computed dispersion interaction energy between carbohydrate and aromatic amino acid residues for RSL wild type and phenylalanine, with values -8.8, -7.9 kcal x mol(-1), excluding the alanine mutant where the interaction energy was -0.9 kcal x mol(-1). Molecular dynamics simulations show that discrepancy can be caused by creation of a new hydrogen bond between the α-L-Me-fucoside and RSL. Observed results suggest that in this and similar cases the carbohydrate-receptor interaction can be driven mainly by a dispersion interaction.
Keywords: lektiny; Protein Binding; proteiny; krystalografie rentgenová; Carbohydrates; mutace; vazebná místa; Bacterial Proteins; Protein Structure, Tertiary; Thermodynamics; terciární struktura proteinů; vodíková vazba; sekundární struktura proteinů; konformace sacharidů; Protein Structure, Secondary; molekulární modely; Crystallography, X-Ray; Models, Molecular; termodynamika; fukosa; vazba proteinů; Binding Sites; konformace proteinů; Lectins; aminokyseliny aromatické; Amino Acids, Aromatic; bakteriální proteiny; Fucose; Protein Conformation; sacharidy; Carbohydrate Conformation; Mutation; Hydrogen Bonding; Proteins; Ralstonia solanacearum